Textbook of forensic science - Shrivastava, Pankaj; Lorente, Jose Antionio; Srivastava, Ankit; Badiye, Ashish; Kapoor, Neeti (Singapore : Springer Nature Singapore, 2023)
"This textbook provides essential and fundamental information to modern forensics investigations. It discusses criminalistics and crime scene aspects, including investigation, management, collecting and packaging various types of physical evidence, forwarding, and chain of custody. It presents fundamental principles, ethics, challenges and criticism of forensic sciences and reviews the crime typologies, the correlates of crime, criminology, penology, and victimology. It provides a viewpoint on legal aspects, including types of evidence, the procedure in the court and scrutiny of the evidence and experts. The book summarizes forensic serological evidences such as blood, semen, saliva, milk-tears, sweat, vaginal fluids, urine, and sweat. It also provides an overview of forensic examination of different types of evidence and also includes comprehensive detailing of forensic ballistics including firearm classification, bullet comparison and matching. Further, it explores the examinations of drugs, chemicals, explosives, and petroleum products. It focuses on the various aspects of forensic toxicology, including the study of various poisons/toxins, associated signs and symptoms, a fatal dose /fatal period of poisons. The book also emphasizes digital and cyber forensics, including classification, data recovery tools, encryption and decryption methods, image, and video forensics. It is a useful resource for graduate and post-graduate students in the field of Forensic Science."
Includes bibliographical references and index/Rujukan : mukasurat
Keywords: Forensic sciences; Crime scene searches; Chemistry, Forensic; Medical jurisprudence; Criminal investigation